LITERATUR REVIEW: PEMBELAJARAN BERDIFERENSIASI SEBAGAI ALTERNATIF PENDEKATAN YANG EFEKTIF - Qibtiyah, Mariyatul; Ahmadi, Anas (Bahtera Indonesia, 2024)
This research aims to analyze the data obtained regarding the implementation of differentiated learning in Indonesian language subjects. The approach used in developing this research was a literature review by conducting a study of 10 journal articles that discussed the implementation of differentiated learning. The results of this research indicate that the urgency of implementing differentiated learning is 1) increasing students' learning motivation; 2) increase creativity according to students' interests; 3) encourage students' learning comfort; 4) encourage achievement of learning objectives; and 5) improve student learning outcomes. Overall, differentiated learning is designed to be preceded by a process of mapping students' character and learning readiness and then producing an effective learning plan.